Flavonoids of Morus, Ficus, and Artocarpus (Moraceae): A review on their antioxidant activity and the influence of climate on their biosynthesis - Dina Hawari, Mutakin Mutakin, Gofarana Wilar, Jutti Levita (Journal of Applied Pharmaceutical Science, 2021)
Moraceae plants are widely distributed in various regions of the world in various climatic conditions. Morus, Ficus, and Artocarpus are the genera of the family Moraceae that have been widely studied for their health benefits such as anti-inflammatory, anticancer, antiplasmodial, antidiabetic, immunomodulator, antispasmodic, and neurodegenerative diseases treatment. These activities are mostly related to the flavonoids that act as natural antioxidants. The flavonoids in plants vary and are influenced by environmental conditions. The objectives of this review were to provide the flavonoids of Morus, Ficus, and Artocarpus (family Moraceae) and their antioxidant activity and to study the influence of the climate on flavonoid biosynthesis. This review includes several studies published in the PubMed database obtained using the keywords (“Morus” OR “Ficus” OR “Artocarpus”) AND “flavonoids” NOT “opuntia” with “full-text” and “10 year” filter. Various classes of flavonoids found in these plants are mostly flavonols and flavones. These three genera of plants also exhibit a strong antioxidant activity through various mechanisms. The flavonoids in Morus, Ficus, and Artocarpus plants are influenced by climatic conditions including temperature and solar radiation by upregulating and downregulating the gene expression involved in flavonoid biosynthesis.
Keywords: Moraceae, flavonoid, antioxidant, climate, biosynthesis.